Identification of a Conserved Gene Signature Associated with an Exacerbated Inflammatory Environment in the Hippocampus of Aging Rats - Pardo, Joaquín (2017)
There have been a few descriptive studies in aged rodents about transcriptome changes in the hippocampus, most of them in males. Here, we assessed the age changes in spatial memory performance and hippocampal morphology in female rats and compared those changes with changes in the hippocampal transcriptome. Old rats displayed significant deficits in spatial memory. In both age groups, hole exploration frequency showed a clear peak at hole 0 (escape hole), but the amplitude of the peak was significantly higher in the young than in the old animals. In the hippocampus, there was a dramatic reduction in neurogenesis, whereas reactive microglial infiltrates revealed an inflammatory hippocampal state in the senile rats. Hippocampal RNA‐sequencing showed that 210 genes are differentially expressed in the senile rats, most of them being downregulated. Our RNA‐Seq data showed that various genes involved in the immune response, including TYROBP, CD11b, C3, CD18, CD4, and CD74, are overexpressed in the hippocampus of aged female rats. Enrichment analysis showed that the pathways overrepresented in the senile rats matched those of an exacerbated inflammatory environment, reinforcing our morphologic findings. After correlating our results with public data of human and mouse hippocampal gene expression, we found an 11‐gene signature of overexpressed genes related to inflammatory processes that was conserved across species. We conclude that age‐related hippocampal deficits in female rats share commonalities between human and rodents. Interestingly, the 11‐gene signature that we identified may represent a cluster of immune and regulatory genes that are deregulated in the hippocampus and possibly other brain regions during aging as well as in some neurodegenerative diseases and low‐grade brain tumors. Our study further supports neuroinflammation as a promising target to treat cognitive dysfunction in old individuals and some brain tumors.